PRINCIPLES OF DAKWAH IN THE QURAN (Treatment Perspective Of Qs Muhammad Verse19) - Ali Mustafa; Elda Ayumi; Mailin Mailin (Universitas Dharmawangsa, 2021)
AbstractGenerally, scholars state that the law of da'wah is obligatory ('ain or kifayah). The problem is, there are opinions that make science a basic condition for preaching. Preaching must be knowledgeable. If that is the case, then how can a Muslim fulfill his duty of preaching? Does he have to wait to memorize and master the Koran 30 juz and thousands of hadiths? What knowledge and in what degree should a preacher master? This paper will answer by making QS Muhammad [47]: 19 as the object of study. Imam Bukhari cited this verse as the main argument in his Sahih when writing the chapter